(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2019)
The present study was carried out with retrospective data collected from the nucleus herd of USDA funded Red Chittagong Cattle (RCC) project at Bangladesh Agricultural University (BAU) and community herd at Char Jailkhana, Mymensingh during 2005 to 2011. The 15 days test interval daily milk yield records of 141 lactations taken from 52 cows from two different herds were collected to estimate multiplicative ratio factors (RF), simple regression from last test day milk yield record (SRLTD) and last test day along with average daily milk yield from known lactation part at any duration (SRLTAD) for prediction of standard 300 days milk yield. The correlations among 300 day milk yields estimated by three different extension models were also investigated and were found no statistically significant differences (P>0.05) with significantly (P<0.01) highly correlated with each other. The results revealed the accuracy of prediction of ratio factors and regression coefficients for three different models and may be adopted any of those models to extend standardized milk production (300 day) for RCC in Bangladesh. Asian Australas. J. Biosci. Biotechnol. 2019, 4 (1), 67-73